PELATIHAN DAN PENDAMPINGAN MASYARAKAT DESA DALAM PEMBUATAN VIDEO PROFIL KAMPUNG KOTA LINTANG KABUPATEN ACEH TAMIANG - Aulia Rahman; Muhammad Taufik Hidayat; Fitria Mustika (LPPM dan PM Universitas Samudra, 2020)
Video profiles are creative and innovative solutions for various needs, especially for the needs of digital media advertising that are popular right now. The expected targets of the community service activities are: (a) Promoting the activities of Lintang City Village in the village profile video that has been posted on the village website; (b) Having a network with organizations working in their respective areas related to making village profile videos so that good cooperation is established between the media and partner organizations; (c) Production of village community profile videos produced from PKM activities. PKM activities are carried out by providing theories related to video making, image capture training, and image processing and video processing training. The service is carried out in three stages, in which the first stage is the preparation stage. In the preparation stage, the service group conducts a preliminary survey to see conditions in the field regarding the making of village profile videos produced by the community. In this stage, solutions and problems faced by the community were given in increasing the ability to produce work on village profile videos. The next stage is the stage of implementing community service activities. In this stage, the servants conducted activities in the form of training in making village profile videos. The last stage is the evaluation stage. At this stage an evaluation of the results achieved by the training participants made a village profile video. Further input and improvements can be made at this stage. Based on the activities that have been carried out, it can be concluded that the training and facilitation of making a profile video of the Lintang City village have been successfully implemented. With the training and facilitation of village community profile videos, it can promote Lintang Town Village activities in the village profile videos that have been posted on the village website.